Identification of Dysregulated Complement Activation Pathways Driven by N-Glycosylation Alterations in T2D Patients - Zhao, Yang; Wang, Man; Meng, Bo; Gao, Ying; Xue, Zhichao; He, Minjun; Jiang, You; Dai, Xinhua; Yan, Dan; Fang, Xiang (Frontiers in Chemistry, 2021)
Diabetes has become a major public health concern worldwide, most of which are type 2 diabetes (T2D). The diagnosis of T2D is commonly based on plasma glucose levels and there are no reliable clinical biomarkers available for early detection. Recent advances in proteome technologies offers new opportunity for the understanding of T2D, however, the underlying proteomic characteristics of T2D have not been thoroughly investigated yet. Here, using proteomic and glycoproteomic profiling, we provided a comprehensive landscape of molecular alterations in the fasting plasma of the 24 Chinese participants, including 8 T2D patients, 8 prediabetes (PDB) subjects, and 8 healthy control (HC) individuals. Our analyses identified a diverse set of potential biomarkers that might enhance the efficiency and accuracy based on current existing biological indicators of (pre)diabetes. Through integrative omics analysis, we showed the capability of glycoproteomics as a complement to proteomics or metabolomics, to provide additional insights into the pathogenesis of (pre)diabetes. We have newly identified systemic site-specific N-glycosylation alterations underlying T2D patients in the complement activation pathways, including decreased levels of N-glycopeptides from C1s, MASP1 and CFP proteins, and increased levels of N-glycopeptides from C2, C4, C4BPA, C4BPB and CFH. These alterations were not observed at proteomic levels, suggesting new opportunities for diagnosis and treatment of this disease. Our results demonstrate a great potential roles of glycoproteomics in understanding (pre)diabetes, and present a new direction for diabetes research which deserving more attention.